Amnesti Umum Nabi Muhammad SAW pada Peristiwa Fathu mekkah - Amin, M. Yakub (POLITEA, 2021)
Fathu Makkah is a historical record of the glory of the Prophet Muhammad who proved the conquest without blood. Fathu Mecca is an authentic proof that general forgiveness or amnesty can be given to the people despite how wrong they were in the past. General Amnesty at the time of Fathu Mecca was proven when not a single blood was shed and unconditional forgiveness was given by the Prophet. The current general amnesty carried out by the international community is no more than a political decision wrapped in rhetoric of peace and humanity. Meanwhile, the Prophet's decision to amnesty was purely due to his humanity and love for peace. There are several points that can be studied at the Fathu Makkah amnesty, namely: Peace Diplomacy Before the Fathu Mecca Incident, Unconditional Forgiveness, Amnesty Fathu Makkah is Better than Amnesty International that Has Been There, The Humanism Attitude of the Prophet in the Fathu Mecca Amnesty